The Influence Of Using Pop-Up Media On Narrative Writing Skills In Indonesian Language Subjects For Class IV Students At SDN 224 Inpres Lekoboddong, Tompobulu District, Maros Regency - Nurhalizah, Ida; Rohana, Rohana; Makkasau, Andi (Program Studi PGSD FIP UNM, 2024)
This research is an experimental research that aims 1) to find out the description of the use of Pop-up media in grade IV of SD Negeri 224 Inpres Lekoboddong, Tompobulu District, Maros Regency, 2) to find out the description of narrative writing skills of grade IV students of SD Negeri 224 Inpres Lekoboddong, Tompobulu District, Maros Regency, and 3) to find out the influence of the use of Pop-up mediaon students' narrative writing skills in Indonesian language learning in grade IV of SD Negeri 224 Inpres Lekoboddong, Tompobulu District, Maros Regency. This type of research is Pre-Experimental Desaign using the One Group Pretest And Posttest Desaign design. The population in this study is all grade IV students of SD Negeri 224 Inpres Lekoboddong totaling 20 people. The research variable consists of an independent variable, namely Pop-up media and a bound variable, namely narrative writing skills. The research procedure is used in two stages, namely the preparation stage and the implementation stage, and the evaluation stage. Data collection techniques This research is observation, test, and documentation. Data was collected by giving Pretest, Treatment, and Posttest. The data analysis technique uses a data prerequisite test, which includes a normality test and a hypothesis test with an actual analysis using a paired sample test with the SPSS system. The results of this study show that 1) the use of Pop-up media for grade IV students at SDN 224 Inpres Lekoboddong is carried out very well in accordance with the steps that have been taken, 2) the narrative writing skills of grade IV students before the treatment is in the category of not good and after being treated are in the category of quite good, 3) the use of Pop-up mediahad a positive effect on students' narrative writing skills in the fourth grade of Indonesian Language at SD Negeri 224 Inpres Lekoboddong, Tompobulu District, Maros Regency.